2023
DOI: 10.1093/eurjpc/zwad063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on cardiac toxicity markers in women with breast cancer undergoing chemotherapy with anthracyclines: a randomized controlled trial

Abstract: Background Exercise training has been suggested to prevent anthracycline-related cardiac dysfunction, but clinical-based evidence is scarce. Aim We investigated the effects of a supervised exercise training program (SETP) on cardiac toxicity markers in women with breast cancer receiving anthracycline-containing chemotherapy. Methods Ninety-three women with ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
6
17
1
Order By: Relevance
“…This study is the first to highlight the individual variation in GLS observed in response to AC treatment and aerobic exercise, although findings are similar to those presented at a group level by Foulkes et al 21 and more recently Antunes et al 39 The same exercise intervention performed in this current study has been shown to improve GLS in women with cardiovascular disease risk factors, 22 which may suggest that other factors, such cumulative AC dose and combination treatment outweigh the potential benefits of aerobic exercise on myocardial function as measured by GLS. Results from this study may also support this suggestion, as after 4-weeks, GLS was improved or maintained from baseline in all participants, potentially indicating an acute positive effect of exercise on GLS.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study is the first to highlight the individual variation in GLS observed in response to AC treatment and aerobic exercise, although findings are similar to those presented at a group level by Foulkes et al 21 and more recently Antunes et al 39 The same exercise intervention performed in this current study has been shown to improve GLS in women with cardiovascular disease risk factors, 22 which may suggest that other factors, such cumulative AC dose and combination treatment outweigh the potential benefits of aerobic exercise on myocardial function as measured by GLS. Results from this study may also support this suggestion, as after 4-weeks, GLS was improved or maintained from baseline in all participants, potentially indicating an acute positive effect of exercise on GLS.…”
Section: Discussionsupporting
confidence: 90%
“…Although not an aim of this study, change in VO 2 peak and GLS did not appear to occur in the same direction, which is again similar to findings from recent randomized controlled trials. 21,39 The reduction in VO 2 peak observed in 2 of the 4 exercising participants does not align with literature supporting the use of exercise to maintain or improve aerobic fitness in women with breast cancer undergoing AC chemotherapy. 20 Participant 2, who experienced the greatest reduction in VO 2 peak upon the completion of DDAC, also scored poorer across multiple symptom domains in comparison to the other 3 exercising participants upon the completion of DDAC treatment (Table 4).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Exercise group: 23%, P = 0.002). The significant benefits observed in maximum voluntary handgrip strength and in the 30-s chair sit-to-stand test, along with the previously reported significant improvement in cardiorespiratory fitness (34), may account for the differences in the number of patients with CMW on the physical functioning domain, between the two groups. In this study, there was also a significant effect of exercise on self-reported cognitive functioning, consistent with the findings from the PACES and OptiTrain trials (35,41).…”
Section: Discussionmentioning
confidence: 73%
“…Regarding the SETP, the mean adherence to training frequency was 63.2 ± 26.9% (73.8 ± 17.8% considering the 32 patients that remained enrolled during chemotherapy) and no serious adverse events were reported during the training sessions (34). Details regarding the safety and tolerability of the SETP are provided elsewhere (34).…”
Section: Resultsmentioning
confidence: 99%